Coastal Vulnerability and Mitigation Strategies From Monitoring to Applied Research - Vicinanza, Diego; Contestabile, Pasquale (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This book is a collection of all papers published in the Special Issue "Coastal Vulnerability and Mitigation Strategies: From Monitoring to Applied Research". The main focus is to provide the state-of-the-art and recent research updates on sustainable management strategies for protecting vulnerable coastal areas. Based on 28 contributions from authors representing 17 different countries (Australia, China, Ecuador, Germany, Greece, India, Italy, Mexico, The Netherlands, New Zealand, Poland, Spain, Sri Lanka, Taiwan, United Arab Emirates, UK, USA), an ensemble of interdisciplinary articles has been collected, emphasizing the importance of tackling technical and scientific problems at different scales and from different point of views.